(untitled) (The Research of Medical Science Review, 2025)
Background: Bell's palsy is an unexpectedly lower motor neuron damage of the facial nerve that causes asymmetry around the mouth, loss of the ability to close the eye, elimination of the nasolabial fold, and destruction of skin creases on the opposite side of the forehead. Bell palsy has a prevalence rate of 15 to 30 per 100,000 people. Objective: To determine the Comparative effects of neuromuscular retraining and mime therapy to treat synkinesis in Bell’s palsy. Material and method: It was a Randomized clinical trial study conducted in 3 clinical hospitals of Faisalabad. 64 participants enrolled in the study by considering the inclusion and exclusion criteria were randomly allocated in two groups by lottery method. Group A received the electrical stimulation and Mime therapy while group B received the electrical stimulation and neuromuscular retaining. Outcome measures of this study were Synkinesis assessment questionnaire and House Brackmann facial grading scale measured the synkinesis and paresis severity in Bell’s palsy patients. Total treatment was of 4 weeks. Data was collected at baseline, after 2nd week and end of treatment at 4th week. Data was be analyzed by using SPSS. Results: The mean age of participants was 37.03±6.85. There was 28 male and 36 female in study. There was significant difference in effect of neuromuscular retraining along with electrical stimulation and mime therapy along with electrical stimulation at end of 4 week of treatment in reducing synkinesis (21.14±2.0 mean rank 14.52 versus 37±10.22 mean rank 41 P =0.000) and improve facial symmetry (1.07±.267 mean rank 17.93 versus 1.89±.567 P= .000). Therefore neuromuscular retraining was more effective in reducing synkinesis and improving facial function in bell’s palsy patients. Conclusion: This study stated that neuromuscular re-training and electrical muscle stimulation had more beneficial effects as compared to mime therapy in decreasing synkinesis and return to normal, symmetrical facial function in Bell’s palsy patients after 4 weeks of treatment.